Stable Nano-Micelles Made of Casein and Keratin Through Self-Assembly - Su, Xiao-Zhou; Wang, Hong-Ru (Asian Journal of Chemistry, 2014)
Nano-micelles made of casein and keratin were produced through self-assembly, the complex micelles were fixed by transglutaminase and became stable. The method for preparing the complex nano-micelles proved to be harmless and green. The nano-micelles behaviour and properties has been investigated in the pH ranges of 5-9. Turbidity measurements, dynamic light scattering, fluorescence measurement, transmission electron and atomic force microscopy studies revealed that the complex nano-micelles have a unique morphology. Their hydrodynamic diameters depend on their behavior under different pH value and mass ratio. The complex nano-micelles had a more stable feature than the casein micelles and can be used to develop environmentally friendly coatings or other biomass materials.